Practical issues in pragmatic trials: the implementation of the Diuretic Comparison Project. (June 2023) - Ferguson, Ryan E; Leatherman, Sarah M; Woods, Patricia; Hau, Cynthia; Lew, Robert; Cushman, William C; Brophy, Mary T; Fiore, Louis; Ishani, Areef
Background/Aims: The US Department of Veterans Affairs Point of Care Clinical Trial Program conducts studies that utilize informatics infrastructure to integrate clinical trial protocols into routine care delivery. The Diuretic Comparison Project compared hydrochlorothiazide to chlorthalidone in reduction of major cardiovascular events in subjects with hypertension. Here we describe the cultural, technical, regulatory, and logistical challenges and solutions that enabled successful implementation of this large pragmatic comparative effectiveness Point of Care clinical trial. Methods: Patients were recruited from 72 Veterans Affairs Healthcare Systems using centralized processes for subject identification, obtaining informed consent, data collection, safety monitoring, site communication, and endpoint identification with minimal perturbation of the local clinical care ecosystem. Patients continued to be managed exclusively by their clinical care providers without protocol specified study visits, treatment recommendations, or data collection extraneous to routine care. Centralized study processes were operationalized through the application layer of the electronic health record via a data coordinating center staffed by clinical nurses, data scientists, and statisticians without site-based research coordinators. Study data was collected from the Veterans Affairs electronic health record supplemented by Medicare and National Death Index data. Results: The study exceeded its enrolled goal (13, 523 subjects) and followed subjects for the 5-year study duration. The key determinant of program success was collaboration between researchers, regulators, clinicians, and administrative staff at the site level to customize study procedures to align with local clinical practice. This flexibility was enabled by designation of the study as minimal risk and determination that clinical care providers were not engaged in research by the Veterans Affairs Central Institutional Review Board. Cultural, regulatory, technical, and logistical problems were identified and solved through iterative collaboration between clinical and research entities. Paramount among these problems was customization of the Veterans Affairs electronic health record and data systems to accommodate study procedures. Conclusions: Leveraging clinical care for large-scale clinical trials is feasible but requires a rethinking of traditional clinical trial design (and regulation) to better meet requirements of clinical care ecosystems. Study designs must accommodate site-specific practice variation to reduce the impact on clinical care. A tradeoff thus exists between designing trial processes tailored to expedite local study implementation versus those to produce a more refined response to the research question. The availability of a uniform and flexible electronic health record in the Department of Veterans Affairs played a major role in the success of the trial. Conducting Point of Care research in other healthcare systems without such research-friendly infrastructure presents a more formidable challenge.